Peripheral and intracerebral T cell immune response in cats naturally infected with Borna disease virus - Berg, Anna-Lena; Johannisson, A.; Johansson, M.; Hein, Andreas; Berg, M.; Dörries, Rüdiger (Veterinary immunology and immunopathology, 1999)
Borna disease virus (BDV) is a neurotropic agent with capacity to cause encephalomyelitis in a wide range of animal species, including horses and cats. Recent studies also point to a link between BDV and human neuropsychiatric disorders. The pathogenesis of Borna disease (BD) has been proposed to be immune-mediated, mainly through the effects of cytotoxic T cells. We used flow cytometric analysis in order to characterize the peripheral and intracerebral T cell immune response in cats naturally infected with BDV. Our results show the presence of two different CD8+ cell populations (CD8+low and CD8+high) in the blood, spleen and brain of these cats. In the brain, CD8+low cells predominated over CD8+high cells. Since CD8+low cells have been suggested to represent a non-MHC-restricted T cell population, the recruitment of such cells to the brains of BDV-infected cats could possibly be of importance for the clearance of virus from neurones.
Gesehen am 30.06.2022